ANALISIS PENGARUH KEPUASAN KERJA, LOYALITAS KERJA, DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN (Studi Pada Bank Indonesia Kota Semarang) - Pradana, Rizky; Nugraheni, Rini (Diponegoro Journal of Management, 2015)
This study is motivated by the performance level of employees at Bank IndonesiaSemarang which has not optimal. Based on interviews pre - survey indicated issues raised by job satisfaction, loyalty, and the work environment to support the process of employee performance. This study aims to examine and analyze the effect of job satisfaction, job loyalty, and non-physical work environment on the performance of employees of Bank Indonesia Semarang. This study uses three independent variables namely job satisfaction, job loyalty, and non-physical work environment with one dependent variable is the performance of employees.This  study  is  applied  toward  50  employees  in  Bank  Indonesia  Semarang  by spreading questionnaires to collect the data eith criteria of respondent minimum 10 years working life. Sampling techniques in this study using purposive sampling method. The data analysis method used in this study include validity, reliability, classic assumption test, multiple linear regression analysis, F test, t test, and the coefficient of determination.Based on the results of t - test and multiple linear regression analysis showed that job satisfaction, job loyalty, and non-physical work environment positive and significant effect on employee performance.The coefficient of determination shows that the performance of employees of Bank Indonesia Semarang influenced by job satisfaction, job loyalty, and non-physical work environment by 74.9% while the remaining 25.1% is influenced by variables - other variables not examined in this study.